Structuring ward rounds to enhance education. (26th August 2019) - Gray, Amy Z; Modak, Maitreyi; Connell, Tom; Enright, Helen
Summary: Background: Ward rounds are a fundamental part of hospital culture and teaching on rounds has a long tradition. Yet evidence points towards increasing difficulties in delivering ward round education in complex heath care settings. Drawing on the literature and gaps identified in our own hospital setting we hypothesised that a tool for structuring ward rounds could improve the educational experience on rounds without adding a time burden to already busy consultants. Methods: We used a developmental evaluation approach to develop a framework and evaluate a tool for improving ward round education. The ward round framework STIC ( S et, T arget, I nspect and Close ) and ward round tool was developed through an iterative process of reviewing and piloting in a clinical department and was evaluated against Moore's outcome levels drawing on quantitative and qualitative data. Surveys of consultants were used to quantify uptake, acceptability and usefulness of the ward round tool. Focus groups of trainee doctors evaluated their experience of ward round education. Results: The majority of consultants used the ward round tool and found it accessible, and useful to enhance education, without extending ward round time. Trainee doctors had seen the ward round tool in use and reflected that it provided structure, focused their learning opportunities, gave clarity to the agenda and provided closure. Unintended benefits were seen for enhanced team work. Conclusions: We present a structured framework STIC and tool for ward rounds that incorporates education, which is acceptable to consultants and is perceived to enhance education for trainees and to strengthen team work. Understanding our framework STIC and our ward round tool's applicability in other settings, scalability and impact and the perspective of patients, would be valuable extensions of this work. We present a structured framework STIC and tool for ward rounds that incorporates education, which is acceptable to consultants and is perceived to enhance education for trainees and to strengthen team work